Developing a nutrition education model based on local wisdom for adolescents to prevent Stunting in the early stage: a preliminary study - Cica Yulia; Delita S Rosdiana; Ellis E Nikmawati; Muktiarni Muktiarni (AcTion: Aceh Nutrition Journal, 2023)
Anemia among adolescents in Indonesia has increased since 2007 until now, as well as worldwide. Anemia had affected their growth and development, along with cognitive abilities, making them susceptible to infectious diseases. Cognitive ability is closely related to the knowledge, attitudes, and behavior of adolescents as internal factors. This study was an introductory study in the development of nutrition education based on local wisdom for adolescents with anemia as early prevention. A qualitative study was conducted in October 2020 in Cirebon District, West Java. The participants consisted of 10 people (eight stakeholders and two experts). Data were collected through focus group discussions and in-depth interviews with instruments as a guide in collecting information data. Data were recorded with the subject's consent, transcribed word for word, and analyzed based on the listed theme by the researcher. Results from the survey stated that using digital development 4,0 learning models will be applied through blended learning and integrated into students' extracurricular activities, using a variety of learning methods and media according to adolescents' development. Thus, this study involved various government sectors to apply the nutrition education model in schools through government policies. Furthermore, it may become a preventive measure for adolescents with anemia.